The Effect of the School Environment on Learning Effectiveness in Elementary School Students - Mutia Ade Syafitri; Putri Amelia Adhari; Tin Rustini (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study was to determine the condition of the elementary school environment, to determine the teacher's role in creating effective and efficient learning in elementary schools, to determine the inhibiting factors of the learning process and to determine the extent to which the school environment influences the effectiveness of learning in elementary schools. The type of research chosen by the researcher is survey research and is a qualitative research by exploring field data using descriptive analysis methods. the study took the research location at SDN Rancairung 1 because it was strategically located, easy to reach and did not require a lot of money, and in collecting data the authors conducted interviews, observations and documentation to complete the required data. The results of this study indicate that in creating effective learning in the classroom the teacher's role is very important because the teacher provides the most services to students when students are at school. Factors that become obstacles to the learning process.